Composition and prognostic significance of T helper lymphocytes in lung cancer - Kivelä, Essi (2024)
Lung cancer is the most fatal cancer worldwide with non-small cell lung cancer and its subtypes adenocarcinoma and squamous cell carcinoma accounting for approximately 80% of all lung cancer cases. In lung cancer treatment immunotherapies, such as PD-L1 checkpoint inhibitors, are widely in use alongside the conventional cancer treatments surgery, radiation, and chemotherapy to improve treatment outcome and survival rate. Immune cell density and composition are heterogenous between tumors and different tumor sites, and research could help better understand the interactions between host tissue and tumor to reveal possible new targets for immunotherapy, as well as new prognostic biomarkers. Multiplex immunohistochemistry enables the use of several monoclonal antibodies for the same tissue section so that many different types of immune cells and their relations to each other to be investigated for effective biomarker research. In the thesis study different subtypes of T lymphocytes, innate lymphoid cells (ILCs), macrophages, and natural killer (NK) cells were stained using specific monoclonal antibodies to calculate respective cell densities within the central tumor and invasive margin of lung cancer tumors. CD8+ and CD4+ T lymphocytes, ILCs, NK cells and macrophages were phenotyped in QuPath bioimage analysis software, while regulatory T lymphocytes, T helper lymphocyte subtypes Th1, Th2, and Th17, and ILC subtypes ILC1, ILC2, and ILC3 were phenotyped by intensity thresholds. Density calculations for each cell type within the tumor center and invasive margin were made. Together with extensive patient data the effect of Th1, Th2, and Th17 on long-term survival was assessed. Th17 was found to have a statistically significant impact on cancer-specific survival three years post operation in the tumor center, and five years post operation both in the tumor center and invasive margin. The findings are, however, contradictory to most results in literature, and more research needs to be made to specify why such results were obtained.